Pepatah masyarakat Sunda sebagai inspirasi desain: Studi kasus pada perancangan body shell mobil pedesaan - Andry Masri; Fred Soritua Rudianto; Amirul Nefo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
The vehicle as an artifact is an object related to humans through sense, so human behavior in using the product is related to the values that will underlie the interpretation that is carried out as behavior directed by attitudes, and the attitude itself is formed by the values held. This raises the consequence that the design of a product to use must consider the values adopted or that apply to the community, which in turn will underlie the design concept of the product itself. This research tries to offer an approach to get a value that applies to a particular society by interpreting the qualities that exist in the proverb or proverb that is used by the people who will receive the product so that it is expected to obtain a visual basic concept that is in accordance with the values that apply to the community. The method used is a qualitative research method with an analytical approach to observing the response to a given visual stimulus. Starting with the collection of sayings that apply to the prospective user community, formulated values adopted by the community are represented based on adjectives. The results of the formulation of values are then translated into visual concepts which are then tested on the community through questionnaires in the form of product image assessment. It was concluded that the community has the ability to capture the design value offered by a product so that a visual concept can be formulated for a design.